2011
DOI: 10.1080/10643381003608268
|View full text |Cite
|
Sign up to set email alerts
|

UV Disinfection of Adenovirus: Present State of the Research and Future Directions

Abstract: Adenoviruses are nonenveloped, double-stranded DNA viruses that infect humans, causing dysentery and respiratory infection. Adenovirus has become a focus of the water treatment community because of its apparent resistance to ultraviolet (UV) disinfection and is the basis for stringent new regulations from the U.S. Environmental Protection Agency regarding UV disinfection of all viruses. Most of the work done so far, however, has involved the use of monochromatic (254 nm) low-pressure UV sources and assay of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Hence, fewer oxidative lesions would be needed to cause inactivation than UVC-induced ones. Alternatively, the discrepancy in the extent of genome damage may point toward the contribution of protein damage to inactivation: as proposed previously by others, monochromatic UVC (254-nm, lowpressure) inactivation is caused almost exclusively by genome damage, whereas polychromatic UV (medium-pressure) inactivation additionally involved protein degradation and hence required a lesser extent of genome damage to achieve the same extent of inactivation (21,(36)(37)(38)(39)(40)(41). In the treatment systems investigated here, this would thus indicate that the contribution of protein damage to inactivation was small for UVC light, greater for full-spectrum solar disinfection, and most prevalent for indirect solar disinfection.…”
Section: Mechanisms Contributing To Solar Disinfection Of Adenovirusmentioning
confidence: 92%
“…Hence, fewer oxidative lesions would be needed to cause inactivation than UVC-induced ones. Alternatively, the discrepancy in the extent of genome damage may point toward the contribution of protein damage to inactivation: as proposed previously by others, monochromatic UVC (254-nm, lowpressure) inactivation is caused almost exclusively by genome damage, whereas polychromatic UV (medium-pressure) inactivation additionally involved protein degradation and hence required a lesser extent of genome damage to achieve the same extent of inactivation (21,(36)(37)(38)(39)(40)(41). In the treatment systems investigated here, this would thus indicate that the contribution of protein damage to inactivation was small for UVC light, greater for full-spectrum solar disinfection, and most prevalent for indirect solar disinfection.…”
Section: Mechanisms Contributing To Solar Disinfection Of Adenovirusmentioning
confidence: 92%
“…AdV is almost always present in sewage (Bradbury et al, 2013), and is the most frequently detected viral pathogen in surface-water and groundwater (Pina et al, 1998;Mena and Gerba, 2009;Bradbury et al, 2013). AdV is more resistant to ultraviolet light and is more stable in environmental waters than most viral pathogens (Eischeid et al, 2011). It can remain infectious for at least one year and its DNA can be detectable in groundwater for as long as 22 months (Charles et al, 2009).…”
mentioning
confidence: 98%
“…A significant amount of data has been published on UV inactivation of adenovirus and other viruses using monochromatic low-pressure (LP) UV followed by assays of infectivity using cell culture; these studies have shown adenovirus to be highly resistant to LP UV disinfection (2). Low-pressure UV is understood to inactivate pathogens by damaging their genomes (4,5).…”
mentioning
confidence: 99%